Role of Deformations in decay of 196Pt formed in 132Sn+64Ni Reaction - Rani, Shweta (My University, 2009)
In view of present day developments in the domain of nuclear physics, it is extremely important & essential to study the nuclear properties and related issues at the extreme conditions of temperature, angular momentum & energies in order to respond the exotic experimentations being conducted & planned in near future. In order to meet such challenges, it becomes extremely essential to update the standard of theoretical computations & as to make meaningful predictions in the related field. It is therefore important to account for the shapes of larger projectile combinations by considering proper deformation & orientation effects. Keeping this in mind, we have investigated the role of deformations & orientation in order to understand nuclear reactions dynamics of 196 Pt formed in 132 Sn+64 Ni. It is reported in literature that the inclusion of deformations & orientations effects change the barrier position & barrier height significantly so as to influence the nuclear decay probabilities. It is relevant to mention here that with the inclusion of such effects barrier
Keywords: Deformations; Fusion Fission